Uses and management of saltmarshes: A global survey. (30th September 2020) - McKinley, E.; Pagès, J.F.; Alexander, M.; Burdon, D.; Martino, S.
Abstract: Saltmarshes are important coastal fringe ecosystems supporting a myriad of coastal uses and users. However, saltmarshes have undergone a significant period of global decline, losing 25%–50% of their coverage due to a range of drivers, but mainly as a result of anthropogenic pressures and land-use change. While the value of these coastal systems to society is recognised, global data are fragmented, patchy, and often restricted to local case studies. There is currently no comprehensive understanding of the global variation of ecosystem services, benefits and management practices available. This pioneering study addresses this by investigating the socio-ecological dimension of global variation in ecosystem service provision, and how this is being managed by and for different saltmarsh users. Through a global online questionnaire survey (n = 438) targeting professional saltmarsh researchers and practitioners representing 40 countries across 5 continents, this paper presents an overview of saltmarsh ecosystem services, key drivers influencing management and the variation in factors that influence them. Analysis indicates considerable variation, with geographical location ('continent') being the most common moderator, influencing perceptions of saltmarshes, the prioritisation of ecosystem services and management perceptions. Finally, the paper presents a series of recommendations, including the development of an interdisciplinary, international research programme to support restoration and conservation of saltmarshes worldwide. Highlights: A global study of saltmarsh stakeholders (n = 438) examining global variation in importance of ecosystem services. Perceived importance of saltmarsh ecosystems services varies with geographical location. This variation has implications for efforts to restore, conserve and maintain saltmarshes. Recommend adoption of a catchment to coast approach to account for multiple values of saltmarshes.